The Image of the Modern Regional Leader: Network Analysis Results - D. I. Kaminchenko (Управленческое консультирование)
The paper is devoted to the analysis of the process of political communication in the conditions of networkization of public space. The sign-symbolic level of political communication is considered on the example of the content-semantic filling of the image of a regional political leader.   The purpose of this research is to analyze the content of the political image of the leader and to identify the presence or absence of manifestation of the effect of networking in it.   The objectives of the study are to study the goals, the principles of their implementation and the features of communication with other representatives of power and society, which are presented in the content of the image of a political leader.   The study uses a set of empirical methods, including non-directional quantitative content-analysis, network data analysis and linguistic analysis. The results of the content analysis are displayed on the tag cloud, and the results of the network analysis are displayed on the thematic graph. The theoretical basis of the study was the theory of the information society and such concepts as “image”, “image-role construct”. According to the results of the study of the text array, which included two large, detailed interviews with the governor of the Nizhny Novgorod region G. S. Nikitin in 2019 and 2020, it was concluded that one of the most common image-role constructs in an interview in 2019 were the following: “leader-industrialist” (aimed at the development of industrial production); “leader-builder” (in particular, he is ready to develop the construction industry of the region); “leader-organizer” (open to new projects and challenges, focused on the successful organization and holding of festive events dedicated to the anniversary of Nizhny Novgorod), “leader-athlete” (advocates for the development of sports in the region). The most common image-role construct in an interview in 2020 was such a meaningful and semantic construct as “leader-manager” (an effective manager who manages the region by coordinating actions with various structural divisions of the government and municipalities). Based on the results of a generalizing analysis, the conclusion was drawn that in the content of the image of a political leader, there was a certain change in the manifestation of the effect of networkization from the polythematic and heterarchy of key topics (in 2019) to the decentralization of the symbolic subject of decision-making and implementation (in 2020).